Human resource planning and human resource development in construction - Tan, Han Leng (2005)
Construction industry is deems to operate by diversify workforce. Hence managing human resource issue deems to be a challenging task. Apparently, Modern SHRM or Strategic Human Resource Management approach in cultivating human resource aspect in order to capitalize human resource towards improvement of project team performance and building organizational competitive advantages. Nonetheless, Project Human Resource Planning and development is an essential portion in managing human resource within a diversifying construction nature. This study carried out in particular to examine the extent of implementation Human Resource Planning and Development in construction project. The core emphasize of the study toward optimizing specific area of organizational planning and team development in enhancing project performance and towards catering the problems faced such as shortage of skilled employees, transient workforce, lack of effective training and performance appraisal. Conclusively, the study of current scenario that ideally the best practice factors are to be considered but only 3 techniques are being practice in reality; the discouraging in practicality of others recommended techniques and tools due to major limitation such as lack of management support. Apparently, the study suggested numerous improvement methods could be adopted to induce the practicality. The study result also indicates through enhancing practicality in Project HR Planning and Development would contribute significant positive impact towards improving construction project performance.